Seasonal nutrient content variation in avocado leaves of ‘Geada’, ‘Fortuna’ and ‘Quintal’ genotypes - Zanata, Renan Moisés Paneghini [UNESP]; Cazetta, Jairo Osvaldo [UNESP]; Barbosa, Paula Wellen Gonçalves [UNESP] (FapUNIFESP (SciELO), 2023)
Avocado is an important fruit for fresh consumption and as raw material for several industries. In order to obtain good productivity and fruit quality, adequate plant nutrition is essential. However, information on the relationship between time of year, phenology and nutritional status of plants of different genotypes is difficult to compare, as most data are obtained from plants of different ages, planted in soils with different fertility levels, different management strategies and most cultivated under edaphoclimatic conditions different from those of Brazil. This study evaluated the seasonal nutrient content variation of avocado leaves, genotypic differences, the relationship with phenological stages and the periods of greater nutrient content stability in ‘Fortuna’, ‘Geada’ and ‘Quintal’ avocado genotypes cultivated in the municipality of Jardinópolis-SP, Brazil. All plants aged 30 years, were randomly planted within the same area and submitted to the same cultural treatments and management. Nutrient contents are more stable during the flowering phase (July to September) and in the final phase of fruit formation (February to March). In most of the cycle, ‘Geada’ plants have lower S, P and Zn levels compared to ‘Fortuna’ and ‘Quintal’ genotypes. ‘Fortuna’ genotype has higher Ca, Mg and Mn levels than the others at the time of fruit harvest (April to June). In the budding phase of the three genotypes (October), increase in N, P, K, S, Cu, Zn contents and decrease in Ca, Mg and Mn contents were observed.
Variação sazonal do teor de nutrientes em folhas de abacateiros dos genótipos Geada, Fortuna e Quintal
Keywords: flowering; fruiting; macronutrients; micronutrients; Persea americana; phenology